Principles Of Landscape – Ecological Planning In The Organisation Of Ecological Network Of Kharkiv Region - Максименко, Н. B.; Квартенко, Р. О. (Man and Environment. Issues of Neoecology, 2014)
The mechanism of landscape ecological planning in the organization of ecological network of Kharkiv region has been revealed. The structure of the landscape and environmental planning process of protected areas which consists of three major steps: landscape analysis, landscape diagnosis and prognosis and activities planning, has been determined. The components of each phase have been described in detail. Spatial comparison of the ecological network structure concerning Kharkiv region’s districts has been made. The perspectives of the territory organization to be attributed to ecological system have been substantiated.”